2021
DOI: 10.1136/jitc-2021-002843
|View full text |Cite
|
Sign up to set email alerts
|

An engineered oncolytic vaccinia virus encoding a single-chain variable fragment against TIGIT induces effective antitumor immunity and synergizes with PD-1 or LAG-3 blockade

Abstract: BackgroundIn addition to directly lysing tumors, oncolytic viruses also induce antitumor immunity by recruiting and activating immune cells in the local tumor microenvironment. However, the activation of the immune cells induced by oncolytic viruses is always accompanied by high-level expression of immune checkpoints in these cells, which may reduce the efficacy of the oncolytic viruses. The aim of this study is to arm the oncolytic vaccinia virus (VV) with immune checkpoint blockade to enhance its antitumor e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…Engineered oncolytic viruses recombinantly expressing monoclonal antibodies against the immunosuppressive molecule TIGIT have been constructed in a previous study. These recombinant oncolytic viruses could turn the “cold” TME to “hot” and induce an effective anti-tumor immune response [ 228 ]. In addition, combination of these viruses with PD-1 inhibitors or LAG-3 inhibitors resulted in better efficacy and caused tumor regression.…”
Section: Advances In Pd-1/pd-l1 Blockade-based Combination Treatment ...mentioning
confidence: 99%
“…Engineered oncolytic viruses recombinantly expressing monoclonal antibodies against the immunosuppressive molecule TIGIT have been constructed in a previous study. These recombinant oncolytic viruses could turn the “cold” TME to “hot” and induce an effective anti-tumor immune response [ 228 ]. In addition, combination of these viruses with PD-1 inhibitors or LAG-3 inhibitors resulted in better efficacy and caused tumor regression.…”
Section: Advances In Pd-1/pd-l1 Blockade-based Combination Treatment ...mentioning
confidence: 99%
“…Even so, solitomab, an EpCAM-CD3 BiTE, was still reported to damage healthy EpCAM + tissues in phase I clinical trials ( 36 , 37 ). Therefore, local administration via an oncolytic virus can avoid the side effects of BiTE ( 38 ). In our study, no significant toxicity was observed during the treatment as monitored by mouse body weight.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the WR strain is the most tumourolytic VV strain in animal models, and 10 6 pfu of WR strain vaccinia virus can rapidly cause subcutaneous necrotic ulcers in rhesus monkeys with no systemic transmission of the virus ( 40 ). Our laboratory uses the WR strain and enhances the tumor-specific selection of vaccinia virus by deleting the thymidine kinase (TK) gene ( 14 , 38 ). Vaccinia viruses lacking the TK gene have been shown to be injected intravenously or intraperitoneally and are carried into subcutaneous tumors where they replicate and cause an anti-tumor response ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…A novel recombinant oncolytic virus VV, VV-α-TIGIT, encoding a fully monoclonal antibody against T cell immunoglobulin and ITIM domain (TIGIT) significantly increased T cell recruitment and activation in the tumor microenvironment [60] . Another engineered oncolytic vaccinia virus, VV-scFv-TIGIT, encoding a single-chain variable fragment (scFv) targeting T-cell immunoglobulin and ITIM domain, induces potent antitumor immunity [61] . Oncolytic viruses expressing antibodies against immune checkpoint domains successfully combine the advantages of OV with an intratumoral expression of ICIs to enhance antitumor efficacy.…”
Section: Oncolytic Virus Combined With Lung Cancer Immunotherapy Stra...mentioning
confidence: 99%